2015
DOI: 10.1080/09168451.2014.1002449
|View full text |Cite
|
Sign up to set email alerts
|

Aβ induces oxidative stress in senescence-accelerated (SAMP8) mice

Abstract: According to the amyloid hypothesis, amyloid β accumulates in brains with Alzheimer’s disease (AD) and triggers cell death and memory deficit. Previously, we developed a rice Aβ vaccine expressing Aβ, which reduced brain Aβ levels in the Tg2576 mouse model of familial AD. We used senescence-accelerated SAMP8 mice as a model of sporadic AD and investigated the relationship between Aβ and oxidative stress. Insoluble Aβ and 4-hydroxynonenal (4-HNE) levels tended to be reduced in SAMP8 mice-fed the rice Aβ vaccine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Oxidative stress would occur when the generation of reactive oxygen species overwhelmed antioxidant enzyme (Huang et al., ). Moreover, oxidative stress induced by Aβ was observed in hippocampal neurons, which was considered to play a critical role in the progression of AD (Takagane et al., ). Thus, we measured antioxidant activity and the levels of oxidized products in the brain of SAMP8 mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress would occur when the generation of reactive oxygen species overwhelmed antioxidant enzyme (Huang et al., ). Moreover, oxidative stress induced by Aβ was observed in hippocampal neurons, which was considered to play a critical role in the progression of AD (Takagane et al., ). Thus, we measured antioxidant activity and the levels of oxidized products in the brain of SAMP8 mice.…”
Section: Resultsmentioning
confidence: 99%
“…It is accepted that β‐amyloid (Aβ) deposition will lead to oxidative stress and finally cause neurodegeneration and cognitive deficits. Increasing evidences suggested that oxidative stress is not only an early event in AD, but also contributes to the neuronal damage (Takagane et al., ). Several studies have shown that age is one of the biggest risk factors for AD and oxidative stress caused by aging is systemic (Gaugler et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Each strain of senescence-accelerated mice shows a strain-specific, aging-like phenotype and exome sequencing reveals the strain-specific mutations that could be responsible for these differences [50]. SAMP8 mice show an age-dependent decrease in the expression of genes that govern mitochondrial integrity and membrane potential, which could affect the fitness of mitochondria upon aging and result in an overall increase of oxidative stress across various organ systems [5156]. Chronic treatments with growth hormone and melatonin have been shown to ameliorate the age-related phenotypes in the SAMP8 mice by targeting the oxidative status [57].…”
Section: Discussionmentioning
confidence: 99%
“…miR-135b has a neuroprotective role in SAMP8 mice. SAMP8 mice are senescence-accelerated and thus have been widely used to investigate AD (14,15). In the present study, miR-135b mimics were injected into the third ventricle of SAMP8 mice to reveal the role of miR-135b in vivo.…”
Section: Mir-135b Promotes the Proliferation Of Hippocampal Cellsmentioning
confidence: 98%